Analisis Ketidaksesuaian Prosedur Penghapusan Aktiva Tetap pada Laporan Keuangan Fiskal PT. MMM - Vania Andani, Jessica; Diarany Sucahyati (P3M Politeknik Negeri Bengkalis, 2025)
This study aims to analyze the discrepancies in the fixed asset write-off procedures in the fiscal financial statements of PT MMM for the 2023–2024 period. The research focuses on identifying errors in the recognition and derecognition of fixed assets, especially related to asset disposal, accumulated depreciation write-off, and profit or loss recognition on asset sales. Using a descriptive qualitative method, data were collected through document analysis, interviews, and supporting evidence such as sales invoices and fixed asset records. The results show that PT MMM failed to implement PSAK 16 principles in the derecognition process. The company did not write off accumulated depreciation and did not calculate the gain or loss on the disposal of fixed assets, resulting in misstated fiscal financial statements. These discrepancies may lead to fiscal corrections and administrative sanctions due to non-compliance with tax reporting requirements. The study concludes that errors in fixed asset write-off procedures stem from a lack of understanding of accounting standards and inadequate documentation. Corrective actions recommended include adjusting accumulated depreciation, recording disposal profit or loss, and ensuring proper derecognition procedures in accordance with PSAK 16 and fiscal regulations. Implementing these improvements is expected to enhance the reliability of financial reporting and prevent potential tax sanctions.